Pengaruh Pendidikan Kesehatan Media Video dan Poster terhadap Pengetahuan dan Sikap Anak dalam Pencegahan Penyakit Diare - Harsismanto J; Eva Oktavidiati; Dina Astuti (Jurnal Kesmas Asclepius, 2019)
This study aims to determine the effect of health education using video and poster media on the knowledge and attitudes of fourth grade SDN 65 Seluma children in preventing diarrhea. This type of research is a quantitative study with a quasi-experimental approach using a two group pre and post test design. The results showed that the average score of children's knowledge in the video media group before the intervention was 68.00, after the intervention was 86.67, the child's attitude before the intervention was 52.67 after being given the intervention 80.93 with ρ-value 0.000. The average score of knowledge in the media poster group before the intervention was 72.67 after the intervention was 87.33, the attitude of the child before the intervention was 42.20 after the intervention was 65.40 with a ρ-value of 0.000. In conclusion, there is a significant effect of health education using video media and posters on children's knowledge and attitudes in preventing diarrhea disease. Keywords: Health Education, Knowledge, Posters, Attitudes, Videos